Age at surgery and outcomes of an undescended testis - Schneuer, F.; Holland, A.; Pereira, Gavin; Jamieson, S.; Bower, C.; Nassar, N. (American Academy of Pediatrics, 2016)
Copyright © 2016 by the American Academy of Pediatrics. BACKGROUND: Undescended testis (UDT) is the most common genital anomaly in boys. Current guidelines recommend surgery before 12 months of age to maximize fertility and potentially reduce the risk of future malignancy. We investigated the prevalence of UDT and examined rates of surgery and age at surgery in an Australian population. METHODS: UDT was identified from all live-born infants in New South Wales, Australia, from 2001 to 2011 using routinely collected record-linked birth and hospital data. The prevalence of UDT, surgery rates, age at surgery, postsurgical outcomes, and risk factors for surgery performed later than the recommended age were evaluated. RESULTS: There were 10 875 (2.1%) boys with a recorded diagnosis of UDT. Corrective surgery was performed in 4980 (45.8%), representing a cumulative prevalence of 9.6 per 1000 male births. Five percent of surgeries were orchidectomies, and 9% of boys had revision surgery. Median age at surgery was 16.6 months (interquartile range 11.8 to 31.0 months), decreasing from 21 months for boys born in 2001 to 13 months for boys born in 2010. Among those boys having surgery before 36 months (n = 3897), 67% had corrective surgery after the recommended 12 months of age; socioeconomic disadvantage, regional/ remote area of residence, and lack of private health insurance were risk factors for having corrective surgery after 12 months. CONCLUSIONS: One in 50 boys born are diagnosed with UDT; two-thirds had no report of corrective surgery. The age at surgery is decreasing; however, two-thirds of surgeries are performed after 12 months of age.